Waste salt-assisted pyrolysis of antibiotic fermentation residue for biochar production and hexavalent chromium reduction mechanism - Yuan Bai; Boxuan Wang; Xin Zhang; Zhihua Chen; Kai Jiang; Dapeng Wu (Bioresource Technology, 2026)

Corrigendum to “Waste salt-assisted pyrolysis of antibiotic fermentation residue for biochar production and hexavalent chromium reduction mechanism” [Bioresou. Technol. 462 (2026) 135547] - Yuan Bai; Boxuan Wang; Xin Zhang; Zhihua Chen; Kai Jiang; Dapeng Wu (Bioresource Technology, 2026)

Spatial decoupling of electron donation and oxygen capture for efficient endogenous oxygen-driven electrosynthesis of 1O2 in water remediation - Xifeng Lu; Pei Su; Jingxuan Zhao; Xuedong Du; Ge Song; Boxuan Cui; Kexin Chen; Qingrui Zhang; Minghua Zhou (Science Bulletin, 2026)

A robust nonlinear model-based controller design for a hybrid wave compensation boarding platform for offshore wind farm operation and maintenance - Boxuan Chen; Lei Tan; Peng Li; Lun Tan; Hongbo Wang; Chaohe Chen (Ocean Engineering, 2026)

Construction and validation of a fast selective catalytic reduction (SCR) strategy for enhancing low-temperature activity of zeolite catalysts under microwave irradiation - Xiangru Li; Yun Chen; Xuehong Zi; Jinyu Yuan; Yao Cheng; Xiaoqian Cheng; Kaiyu Hu; Boxuan Song; Wenjun Liang; Liyun Song (Journal of Environmental Chemical Engineering, 2026)

Fuzzy Neural Broad Learning System: Data-Driven Model Predictive Control for Shipboard Boarding Systems - Lun Tan; Chaohe Chen; Xinkuan Yan; Boxuan Chen; Jianhu Fang (Journal of Marine Science and Engineering, 2026)
Shipboard boarding systems operating under complex sea conditions are subject to vessel motion coupling, wave induced disturbances, strong nonlinearity, and engineering constraints, which make accurate end pose tracking difficult. Existing mechanism-based approaches often suffer from modeling inaccuracies and high online computational burden, whereas purely data driven methods usually provide limited interpretability for safety critical marine applications. To address these limitations, this paper proposes a data driven predictive control method for shipboard boarding systems based on a Fuzzy Neural Broad Learning System. An interpretable Linear Regression Decision Tree is first constructed to represent the plant through state space partition and local linear approximation. On this basis, a Fuzzy Neural Broad Learning predictor is developed to capture disturbance-induced uncertainty and parameter variation with fast analytical training and incremental updating capability. The predictor is then embedded into a constrained model-predictive control framework in which actuator saturation, input rate limits, and output safety constraints are handled explicitly, and closed-loop boundedness is analyzed theoretically. Simulation results on a MATLAB R2024a-based and Simulink-based coupled platform show that, for the translational outputs of the gangway end effector, the testing root mean square error ranges from 1.33 × 10−3 to 1.74 × 10−3, with corresponding coefficients of determination ranging from 0.820 to 0.912. In comparative closed-loop simulations against proportional integral derivative control, fuzzy control, and learning-based control under identical operating conditions, the proposed method achieves the lowest integral of squared error and integral of absolute error, reaching 3.40 × 10−7 and 4.28 × 10−4, respectively. Compared with the best value among the three baseline controllers, the proposed method reduces the integral of squared error by approximately 42.6% and the integral of absolute error by approximately 34.4%. Although its maximum deviation is not the smallest among all compared controllers, it remains within the same order of magnitude as the advanced baselines. In addition, the average and maximum per-step computation times are 1.61 × 10−4 s and 3.75 × 10−3 s, respectively, both of which are far below the adopted sampling period of 0.05 s. These results indicate that the proposed framework improves cumulative tracking accuracy while maintaining feasible online computational performance.

Long-term organic amendments regulate cbbL-harboring bacterial community via soil physicochemical properties and enzyme activities in a paddy soil - Jiangbing Xu; Boxuan Li; Yuhao Wu; Lei Liu; Guoyi Zhou; Xiaoli Liu; Ling Chen; Meng Wu; Xiaoyan Ma; Catherine Preece; Daming Li; Ming Liu (Journal of Soils and Sediments, 2026)

Impact of equivalence ratio on soot emissions from turbofan combustor during takeoff and ground idle status - Guangze Li; Zhenzhong Zhang; Liuyong Chang; Ragui Karim; Yiwei Zhao; Boxuan Cui; Longfei Chen; Ye Kang; Lei He (Journal of Aerosol Science, 2026)

Deep learning-based morphological analysis of human sperm - Yiran Xu; Yuqiu Chen; Boxuan Zhang; Yimo Yan; Hongen Liao; Ran Liu (Medical & Biological Engineering & Computing, 2026)